Rodziny rolnicze o niskich dochodach - Gralak, Arkadiusz; Stańko, Stanisław (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 1998)
The research comprises analysis of scale and scope of low income level consequences in agricultural households in 1996. For the purpose of the analysis, agricultural holdings are allocate to two groups of poverty on the basis of disposable income level. First one consists holdings with disposable income per person below an adequate income level (so call d minimum-subsistence income); the second one - holdings with income per member of family below minimum social income. The outcome of the study shows that on average 48.83 per cent of families operating agricultural holdings lies in poverty, of which 33.6 per cent in misery and 15.23 per cent in extreme poverty. Poverty widespread differs according to the number of family members, by regions and sources of incomes. The people working on farms are most stuck below an poverty line. Poverty is more common in the north macroregion of Poland, however in the central-west macroregion of the country it is observed to be the least extended. Main source of income in poor families constitute social payments (pensions, retirement benefits, social benefits) amounted to 55.7 per cent of their disposable income, off-farm work and agricultural activity (20.43 and 21.73 per cent respectively). Better situated farm families earn their living first of all by agricultural activity, that brings them 73.45 per cent of their disposable income. Bath social payments and paid employment are supplementary sources of their income (11. 78 and 10.49 per cent respectively).